Formula Expression of Airgap Leakage flux Coefficient of Axial-Flux Permanent Magnet Motor - Xiao Gong; Yanliang Xu; Feng Xin (Universitas Ahmad Dahlan, 2013)
Airgap leakage flux coefficient is one of the main parameters which must be given ahead of time when performing initial designs or getting performance results by magnetic circuit analysis for any kinds of electrical machines. Three -dimensional finite element method (3D-FEM) is the most reliable one to obtain the accurate leakage flux coefficient for axial-flux permanent magnet (AFPM) motor which definitely takes a much long time and is not advantageous to the motor’s initial and optimal design. By constituting the accurate lumped-parameter magnetic circuit (LPMC) model and computing the resultant magnetic reluctances, the analytical formula of the leakage flux coefficient of AFPM is given which is verified by 3D-FEM and the prototyped AFPM experiment.